Respuesta :
[tex]\underbrace{(4x+3y^2)}_M\,\mathrm dx+\underbrace{2xy}_N\,\mathrm dy=0[/tex]
The ODE is exact if [tex]\dfrac{\partial M}{\partial y}=\dfrac{\partial N}{\partial x}[/tex].
[tex]M_y=6y[/tex]
[tex]N_x=2y[/tex]
This is not the case, so look for an integrating factor [tex]\mu(x)[/tex] such that
[tex]\dfrac\partial{\partial y}\mu M=\dfrac\partial{\partial x}\mu N[/tex]
Since [tex]\mu[/tex] is a function of [tex]x[/tex] only, you have
[tex]\mu M_y=\mu'N+\mu N_x\implies\dfrac{\mu'}\mu=\dfrac{M_y-N_x}N\implies\mu=\exp\left(\displaystyle\int\frac{M_y-N_x}N\,\mathrm dx\right)[/tex]
So, the integrating factor is
[tex]\mu=\exp\left(\displaystyle\int\frac{6y-2y}{2xy}\,\mathrm dx\right)=\exp\left(2\int\frac{\mathrm dx}x\right)=x^2[/tex]
Now the ODE can be modified as
[tex]\underbrace{(4x^3+3x^2y^2)}_{M^*}\,\mathrm dx+\underbrace{2x^3y}_{N^*}\,\mathrm dy=0[/tex]
Check for exactness:
[tex]{M^*}_y=6x^2y[/tex]
[tex]{N^*}_x=6x^2y[/tex]
so the modified ODE is indeed exact.
Now, you're looking for a solution of the form [tex]\Psi(x,y)=C[/tex], since differentiating via the chain rule yields
[tex]\dfrac{\mathrm d}{\mathrm dx}\Psi(x,y)=\Psi_x+\Psi_y\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
Matching up components, you would have
[tex]\Psi_x=M^*=4x^3+3x^2y^2[/tex]
[tex]\displaystyle\int\Psi_x\,\mathrm dx=\int(4x^3+3x^2y^2)\,\mathrm dx[/tex]
[tex]\Psi=x^4+x^3y^2+f(y)[/tex]
Differentiate this with respect to [tex]y[/tex] to get
[tex]\Psi_y=2x^3y+f'(y)=2x^3y=N^*[/tex]
[tex]f'(y)=0\implies f(y)=C_1[/tex]
So the solution here is
[tex]\Psi(x,y)=x^4+x^3y^2+C_1=C\implies x^4+x^3y^2=C[/tex]
Just for a final check, take the derivative to get back the original ODE:
[tex]\dfrac{\mathrm d}{\mathrm dx}[x^4+x^3y^2]=\dfrac{\mathrm d}{\mathrm dx}C[/tex]
[tex]4x^3+3x^2y^2+2x^3y\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
[tex]4x+3y^2+2xy\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
[tex](4x+3y^2)\,\mathrm dx+2xy\,\mathrm dy=0[/tex]
so the solution is correct.
The ODE is exact if [tex]\dfrac{\partial M}{\partial y}=\dfrac{\partial N}{\partial x}[/tex].
[tex]M_y=6y[/tex]
[tex]N_x=2y[/tex]
This is not the case, so look for an integrating factor [tex]\mu(x)[/tex] such that
[tex]\dfrac\partial{\partial y}\mu M=\dfrac\partial{\partial x}\mu N[/tex]
Since [tex]\mu[/tex] is a function of [tex]x[/tex] only, you have
[tex]\mu M_y=\mu'N+\mu N_x\implies\dfrac{\mu'}\mu=\dfrac{M_y-N_x}N\implies\mu=\exp\left(\displaystyle\int\frac{M_y-N_x}N\,\mathrm dx\right)[/tex]
So, the integrating factor is
[tex]\mu=\exp\left(\displaystyle\int\frac{6y-2y}{2xy}\,\mathrm dx\right)=\exp\left(2\int\frac{\mathrm dx}x\right)=x^2[/tex]
Now the ODE can be modified as
[tex]\underbrace{(4x^3+3x^2y^2)}_{M^*}\,\mathrm dx+\underbrace{2x^3y}_{N^*}\,\mathrm dy=0[/tex]
Check for exactness:
[tex]{M^*}_y=6x^2y[/tex]
[tex]{N^*}_x=6x^2y[/tex]
so the modified ODE is indeed exact.
Now, you're looking for a solution of the form [tex]\Psi(x,y)=C[/tex], since differentiating via the chain rule yields
[tex]\dfrac{\mathrm d}{\mathrm dx}\Psi(x,y)=\Psi_x+\Psi_y\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
Matching up components, you would have
[tex]\Psi_x=M^*=4x^3+3x^2y^2[/tex]
[tex]\displaystyle\int\Psi_x\,\mathrm dx=\int(4x^3+3x^2y^2)\,\mathrm dx[/tex]
[tex]\Psi=x^4+x^3y^2+f(y)[/tex]
Differentiate this with respect to [tex]y[/tex] to get
[tex]\Psi_y=2x^3y+f'(y)=2x^3y=N^*[/tex]
[tex]f'(y)=0\implies f(y)=C_1[/tex]
So the solution here is
[tex]\Psi(x,y)=x^4+x^3y^2+C_1=C\implies x^4+x^3y^2=C[/tex]
Just for a final check, take the derivative to get back the original ODE:
[tex]\dfrac{\mathrm d}{\mathrm dx}[x^4+x^3y^2]=\dfrac{\mathrm d}{\mathrm dx}C[/tex]
[tex]4x^3+3x^2y^2+2x^3y\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
[tex]4x+3y^2+2xy\dfrac{\mathrm dy}{\mathrm dx}=0[/tex]
[tex](4x+3y^2)\,\mathrm dx+2xy\,\mathrm dy=0[/tex]
so the solution is correct.